Impact of El Niño Southern Oscillation on the first inter-monsoon rainfall over Sri Lanka in the post-El Niño years - Ranaweera, K. R. K. D. Nadeeka; Kamae, Youichi (Frontiers in Climate, 2024)
Sri Lanka has a tropical monsoon climate. The first intermonsoon (FIM) season is one of four rainfall seasons. Previous investigations have explored the concurrent ramifications of the El Niño Southern Oscillation (ENSO); however, its impact on seasonal rainfall patterns in the country in the post-El Niño years remains unexplored. This study aims to investigate anomalous FIM rainfall in Sri Lanka during the post-El Niño years. Weather station rainfall data from the Department of Meteorology for 114 stations for 1975-2019, Japanese 55-year reanalysis data, and COBE sea surface temperature data were used in this study. A significant negative correlation between rainfall at most stations and the preceding year's November, December, and January Niño3.4 index (NDJ Niño3.4) was identified for the FIM season. All three super El Niño events and one of the two strong El Niño events agree with the above results, showing a clear negative rainfall anomaly pattern. The Indo-western Pacific Ocean Capacitor effect was identified as the cause of rainfall reduction during the FIM season in Sri Lanka and in contrast, the post-El Niño season in 1988 exhibited a positive rainfall anomaly. A rapid transition from El Niño to La Niña and the associated atmospheric conditions were identified as significant contributors to these features. The findings of this study will help overcome this research gap and improve the accuracy of seasonal forecasts for the country.